2013
DOI: 10.1016/j.ridd.2013.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-determined physical activity and walking capacity in persons with Down syndrome, Williams syndrome and Prader–Willi syndrome

Abstract: In this study we describe by use of accelerometers the total physical activity (PA), intensity pattern and walking capacity in 87 persons age 16-45 years with Down syndrome (DS), Williams syndrome (WS) and Prader-Willi syndrome (PWS). Participants were recruited from all over Norway, and lived either with their parents or in community residences with support. On average the participants generated 294 counts per minute (cpm) or 6712 steps per day, with most of the day spent in sedentary activity, 522 min/day, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 39 publications
6
97
1
5
Order By: Relevance
“…Interestingly, also the number of breaks in sedentary activity was reduced and longer periods of rest were observed. The resting percentage found in our study was comparable to the resting percentage in ambulatory normally weighted children with Down's-, William's-and Prader-Willi syndrome (Nordstrom et al 2013) and patients with CP, when both patient groups were stratified based on their walking abilities (Gorter et al 2012). Five young ambulatory boys (4-6 years) with Duchenne Muscular Dystrophy (DMD) (Jeannet et al 2011), who were significantly younger than our study subjects, spent much less time resting, but had comparable levels of dynamic activity when compared to our ambulatory patients.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, also the number of breaks in sedentary activity was reduced and longer periods of rest were observed. The resting percentage found in our study was comparable to the resting percentage in ambulatory normally weighted children with Down's-, William's-and Prader-Willi syndrome (Nordstrom et al 2013) and patients with CP, when both patient groups were stratified based on their walking abilities (Gorter et al 2012). Five young ambulatory boys (4-6 years) with Duchenne Muscular Dystrophy (DMD) (Jeannet et al 2011), who were significantly younger than our study subjects, spent much less time resting, but had comparable levels of dynamic activity when compared to our ambulatory patients.…”
Section: Discussionsupporting
confidence: 82%
“…However, the minimum wear time required for inclusion in the analysis varied across the eight studies. In six studies the wear time cut-off for inclusion was three days of six hours 20-23;33;34 , one study required four days of 10 hours wear time for inclusion 32 and two studies did not report the minimum wear time required for inclusion. 30;31 The cut-off used to define sedentary behaviour based on accelerometer counts also differed across studies.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…Researchers in Norway examined accelerometerdetermined physical activity and sedentary behaviour in a large sample of adults with Down syndrome, Williams syndrome, and Prader-Willi syndrome; all genetic conditions associated with intellectual disabilities. 6 These authors found that individuals spent 63% of their day in sedentary activity and 3% in moderate to vigorous intensity physical activity. Although on average individuals accrued 27 minutes per day of moderate to vigorous physical activity, overall only 12% of the sample met the Nordic recommendations of physical activity.…”
mentioning
confidence: 99%